2004
DOI: 10.1191/0269216304pm941oa
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in palliative care: patient perspectives

Abstract: This qualitative study investigated the meaning of sexuality to palliative patients. Face-to-face interviews were conducted with ten patients receiving care in a tertiary palliative care unit, a hospice or by palliative home care services in their homes. Several themes emerged. Emotional connection to others was an integral component of sexuality, taking precedence over physical expressions. Sexuality continues to be important at the end of life. Lack of privacy, shared rooms, staff intrusion and single beds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 13 publications
3
117
2
5
Order By: Relevance
“…This is a highly unusual situation as studies consistently indicate a marked reluctance on the part of many health workers to discuss patients' sexual concerns (e.g. Kedde, van de Wiel, Schultz, Vanwesenbeeck & Bender, 2012;Lemieux, Kaiser, Pereira & Meadows, 2004;Stead, Fallowfield, Brown & Selby, 2001), and its benefits, in terms of quality and continuity of care, should not be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…This is a highly unusual situation as studies consistently indicate a marked reluctance on the part of many health workers to discuss patients' sexual concerns (e.g. Kedde, van de Wiel, Schultz, Vanwesenbeeck & Bender, 2012;Lemieux, Kaiser, Pereira & Meadows, 2004;Stead, Fallowfield, Brown & Selby, 2001), and its benefits, in terms of quality and continuity of care, should not be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Jootun, McGhee, and Marland (2009) argue that the inclusion of a reflexive account should be part of qualitative enquiry to increase the rigour of the research process and add credibility. Only one study (Lemieux, Kaiser, Pereira, & Meadows, 2004) described the researchers as having made their biases explicit during the data collection phase, however these were not expanded on within the text; none of the other studies reported on the relationship between the researcher(s) and participants. None of the studies reported their epistemological or ontological perspectives.…”
Section: Tablementioning
confidence: 99%
“…Three studies offered an account of participants perceiving staff as unwilling to engage with discussions around sexuality (Brown et al, 2014;Lemieux et al, 2004;Östman, 2008), suggesting that the approach of care staff moderated how sexuality was discussed.…”
Section: Privates Are Private "But Deeper Things You Can't Talk Tomentioning
confidence: 99%
See 2 more Smart Citations